Nuclear export of the influenza virus ribonucleoprotein complex: Interaction of Hsc70 with viral proteins M1 and NS2 - Ken Watanabe; Teppei Shimizu; Saiko Noda; Fujiko Tsukahara; Yoshiro Maru; Nobuyuki Kobayashi (FEBS Open Bio, 2014)
The influenza virus replicates in the host cell nucleus, and the progeny viral ribonucleoprotein complex (vRNP) is exported to the cytoplasm prior to maturation. NS2 has a nuclear export signal that mediates the nuclear export of vRNP by the vRNP–M1–NS2 complex. We previously reported that the heat shock cognate 70 (Hsc70) protein binds to M1 protein and mediates vRNP export. However, the interactions among M1, NS2, and Hsc70 are poorly understood. In the present study, we demonstrate that Hsc70 interacts with M1 more strongly than with NS2 and competes with NS2 for M1 binding, suggesting an important role of Hsc70 in the nuclear export of vRNP.